Use of an electronic decision support tool to reduce polypharmacy in elderly people with chronic diseases: cluster randomised controlled trial. (18th June 2020) - Rieckert, Anja; Reeves, David; Altiner, Attila; Drewelow, Eva; Esmail, Aneez; Flamm, Maria; Hann, Mark; Johansson, Tim; Klaassen-Mielke, Renate; Kunnamo, Ilkka; Löffler, Christin; Piccoliori, Giuliano; et al.
Abstract: Objective: To evaluate the effects of a computerised decision support tool for comprehensive drug review in elderly people with polypharmacy. Design: Pragmatic, multicentre, cluster randomised controlled trial. Setting: 359 general practices in Austria, Germany, Italy, and the United Kingdom. Participants: 3904 adults aged 75 years and older using eight or more drugs on a regular basis, recruited by their general practitioner. Intervention: A newly developed electronic decision support tool comprising a comprehensive drug review to support general practitioners in deprescribing potentially inappropriate and non-evidence based drugs. Doctors were randomly allocated to either the electronic decision support tool or to provide treatment as usual. Main outcome measures: The primary outcome was the composite of unplanned hospital admission or death by 24 months. The key secondary outcome was reduction in the number of drugs. Results: 3904 adults were enrolled between January and October 2015. 181 practices and 1953 participants were assigned to electronic decision support (intervention group) and 178 practices and 1951 participants to treatment as usual (control group). The primary outcome (composite of unplanned hospital admission or death by 24 months) occurred in 871 (44.6%) participants in the intervention group and 944 (48.4%) in the control group. In an intention-to-treat analysis the odds ratio of the composite outcome was 0.88 (95% confidence interval 0.73 to 1.07; P=0.19, 997 of 1953 v 1055 of 1951). In an analysis restricted to participants attending practice according to protocol, a difference was found favouring the intervention (odds ratio 0.82, 95% confidence interval 0.68 to 0.98; 774 of 1682 v 873 of 1712, P=0.03). By 24 months the number of prescribed drugs had decreased in the intervention group compared with control group (uncontrolled mean change −0.42 v 0.06: adjusted mean difference −0.45, 95% confidence interval −0.63 to −0.26; P<0.001). Conclusions: In intention-to-treat analysis, a computerised decision support tool for comprehensive drug review of elderly people with polypharmacy showed no conclusive effects on the composite of unplanned hospital admission or death by 24 months. Nonetheless, a reduction in drugs was achieved without detriment to patient outcomes. Trial registration: Current Controlled Trials ISRCTN10137559 .